Activation energy of the growth of ion-beam-synthesized nano-crystalline 3C-SiC - S. Intarasiri (2018)
In this experiment, carbon ions at 40 keV were implanted into (1 0 0) high-purity p-type silicon wafers at 400 °C to a fluence of 6.5 × 1017ions/cm2. Subsequent thermal annealing of the implanted samples was performed in a vacuum furnace at 800-1000 °C. Glancing incidence X-ray diffraction (GIXRD) was used to characterize the crystalline quality and estimate the grain size of nano-crystalline 3C-SiC. Activation energy for the growth of 3C-SiC was evaluated following the annealing behaviour of the GIXRD-characteristic 3C-SiC (1 1 1) peaks. It was found that the 3C-SiC was directly formed during ion implantation at this substrate temperature and the activation energy of the process was about 0.05 eV. Such a low energy was explained in terms of ion beam induced precipitate formation. © 2007 Elsevier B.V. All rights reserved.